Financial Networks, Cross Holdings, and Limited Liability - Helmut Elsinger (Oesterreichische Nationalbank (OeNB), 2009)
I discuss a network of banks which are linked with each other by financial obligations and cross holdings. Given an initial endowment the value of the obligations and the equity values of the banks are determined endogenously in a way consistent with the priority of debt and the limited liability of equity. Even though neither equity values nor debt values are necessarily unique the value of debt and equity holdings of outside investors is uniquely determined. An algorithm to calculate debt and equity values is developed.
Keywords: G21; G33; 330; Financial Network; Credit Risk; Systemic Risk